Strategi Komisi Pemilihan Umum Kota Jakarta Selatan Dalam Meningkatkan Partisipasi Pemilih Pada Pemilu Tahun 2024 - Anandita Azzahra; Ridwan Ridwan (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Voter participation is a key element in the implementation of elections and is a benchmark for ideal democracy. However, fluctuating voter participation rates demand effective strategies from election organizers. This study aims to analyze and describe the strategies implemented by the South Jakarta City General Elections Commission (KPU) to increase voter participation in the 2024 Election. The research method used is descriptive qualitative, utilizing primary data sources from field research (interviews and observations) and secondary data in the form of a literature review. Data analysis uses Peter Schroder's theory of political strategy, which divides them into offensive and defensive strategies. The results of this study indicate that the offensive and defensive strategies implemented by the South Jakarta City KPU are effective in increasing voter participation, particularly through education-based communication strategies and digital media. The offensive strategy is realized through face-to-face socialization, the use of social media, and the dissemination of information through various media. Meanwhile, defensive strategies are implemented through cross-institutional coordination and collaboration, including educational and government institutions to maintain public trust. The synergy of these two strategies has succeeded in making South Jakarta the highest voter participation rate in DKI Jakarta Province. The South Jakarta City KPU has succeeded not only in increasing participation quantitatively but also creating a participatory and sustainable democratic system.